2014
DOI: 10.1007/s10549-014-3217-y
|View full text |Cite
|
Sign up to set email alerts
|

Phase III study on efficacy of taxanes plus bevacizumab with or without capecitabine as first-line chemotherapy in metastatic breast cancer

Abstract: Taxanes (T) plus bevacizumab (B) and taxanes plus capecitabine (X) showed better progression-free survival (PFS) compared to taxanes alone. Since life-threatening or highly symptomatic situations require polychemotherapy in metastatic breast cancer (MBC), combination of taxanes, capecitabine plus bevacizumab appears reasonable. TABEA (NCT01200212), a prospectively randomized, open-label, phase III trial compares taxanes (paclitaxel 80 mg/m(2) i.v. d1,8,15 q22 or docetaxel 75 mg/m(2) i.v. d1 q22) plus bevacizum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 15 publications
0
22
0
Order By: Relevance
“…In contrast, a meta-analysis of phase III trials found that combination chemotherapy regiments showed a better time to progression, but not overall survival, in metastatic BC patients [17]. Similarly, it was noticed that a combined schedule, for instance, taxanes (paclitaxel or docetaxel) plus bevacizumab, displayed a higher progression-free survival versus taxanes alone (10 vs. 13.3 months; p = 0.474) as first line chemotherapy in metastatic BC [18]. Nonetheless, in spite of several schedule options, patients frequently relapse after chemotherapy treatment as a result of the acquired resistance of the tumor cells or by signals drivens by the microenvironment in order to enhance the cancer stem cells which are resistant to different treatments [19].…”
Section: Main Textmentioning
confidence: 99%
“…In contrast, a meta-analysis of phase III trials found that combination chemotherapy regiments showed a better time to progression, but not overall survival, in metastatic BC patients [17]. Similarly, it was noticed that a combined schedule, for instance, taxanes (paclitaxel or docetaxel) plus bevacizumab, displayed a higher progression-free survival versus taxanes alone (10 vs. 13.3 months; p = 0.474) as first line chemotherapy in metastatic BC [18]. Nonetheless, in spite of several schedule options, patients frequently relapse after chemotherapy treatment as a result of the acquired resistance of the tumor cells or by signals drivens by the microenvironment in order to enhance the cancer stem cells which are resistant to different treatments [19].…”
Section: Main Textmentioning
confidence: 99%
“…Based on the search strategy, 7 eligible trials with a total of 3,984 patients were identified and included in this meta-analysis (Figure S1). 12,13,1620 The details of these included studies are summarized in Table 1. Three of these studies were used to evaluate the efficacy of adding bevacizumab to chemotherapy, including 1,558 women who received bevacizumab combined with chemo-therapy and 896 women who were administered chemotherapy alone 12,13,17.…”
Section: Resultsmentioning
confidence: 99%
“…Three of these studies were used to evaluate the efficacy of adding bevacizumab to chemotherapy, including 1,558 women who received bevacizumab combined with chemo-therapy and 896 women who were administered chemotherapy alone 12,13,17. The other 4 trials were obtained to assess the optimal chemotherapy partner of bevacizumab 16,1820. All of them were published as full articles and described as Phase III randomized controlled trials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficacy of antiangiogenic agents in several types of cancer was also examined, and some were used at a clinical level. [13][14][15] Most recently, inhibition of immunological checkpoints such as cytotoxic T lymphocyte-associated protein 4 (CTLA-4) and programmed cell death 1 (PD-1) molecules produced long-lasting antitumor effects, and consequently, we realized that immunotherapy can play a central role in cancer treatment. 16 Similarly, an investigation into MPM at the molecular level led to several clinical trials with molecular-targeted agents.…”
Section: Current Therapy For Mesotheliomamentioning
confidence: 99%